Digital technologies in music education − The prospects of interactive course development in primary school music education (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2021)
Within the framework of the 'Education Innovation - Modernisation of the training structure, methods and content in higher education, enhancement of its labour market relevance', we conducted a course material development project for the length of two terms at the Institute of Education and Social Sciences, Apáczai Csere János Faculty of Humanities, Széchenyi István University. We devised course material to be applied in e-learning and in a place-based studying environment (VR course material). The aim of the project was to create support material that assists teacher candidates in processing and acquiring the material of primary school music education. Its necessity and timeliness are justified by the insufficient level of music skills of newly admitted teacher candidates. The present paper is intended to display a summary and short-term evaluation of the project.